Potensi Dan Pengembangan Wellness Tourism Di Kabupaten Bangka Tengah: Kajian Literatur Berbasis Sumber Daya Alam Dan Kearifan Lokal - devy (Institut Citra Internasional, 2026)
Wellness tourism has emerged as one of the fastest-growing segments in global tourism, fueled by the increasing awareness of holistic health encompassing physical, mental, spiritual, and social dimensions. Bangka Tengah Regency, as part of the Bangka Belitung Islands Province, possesses substantial natural resources and local wisdom that can be developed into competitive and sustainable wellness tourism products. This study aims to: (1) identify the natural and cultural resources of Bangka Tengah relevant to wellness tourism development; (2) examine conceptual frameworks of wellness tourism applicable to the local context; and (3) formulate wellness tourism development strategies grounded in the local wisdom of Bangka Tengah. . The method used is a systematic literature study of 47 scientific literature sources collected through the Google Scholar and SINTA databases, including international and national journals related to wellness tourism, nature-based tourism, and destination development. Of these, 28 literatures were deemed most relevant and used substantively in the analysis, with relevance criteria including thematic suitability, publication novelty (2013-2024), and nature-based destinations. The results of the study indicate that water-based natural aspects, especially revitalized ex-mining beaches and lakes, are the most dominant elements and most ready to be developed as wellness tourism attractions. In addition, the bedulang tradition as a communal eating practice based on communal values ​​and local herbal wisdom is the most distinctive cultural asset and is difficult to replicate in other destinations, thus becoming a major comparative advantage. Mangrove forests are in third place as nature-based ecotherapy and mindfulness spaces. This research has direct implications for three parties: (1) for the local government, the results of this study can be the basis for formulating wellness area zoning policies and destination development roadmaps; (2) for tourism business actors, these findings offer concrete guidance in designing authentic and competitive wellness tourism packages; (3) for local communities, the development of wellness tourism based on local wisdom has the potential to open up new job opportunities while strengthening the preservation of Central Bangka's cultural traditions.